Efficacy Of Kinesiology Taping Versus Interferential Therapy On Mechanical Neck Pain - R, Sindhuja; P, Sudhesh; K, Soundararajan; Caleb, Jerry; G, Velmurugan; M, Soundharya (Journal of Neonatal Surgery, 2025)
Background: Neck pain is a prevalent issue experienced by individuals of all ages. Mechanical neck pain refers to generalized discomfort in the neck, triggered by sustained postures, neck movements, and tenderness in the cervical muscles, without underlying pathologies. It is most common in middle-aged individuals. Kinesiology taping is a therapeutic method used to support muscles, joints, and fascia, promoting a full range of motion and aiding in the reduction of inflammation and pain, which is believed to accelerate recovery from injuries or micro-traumas. This effect is thought to occur by stimulating the body's natural healing processes and calming the nervous system. However, research on the application of kinesiology taping for mechanical neck pain is limited. This study aims to investigate this technique and compare its effectiveness to traditional physiotherapy in terms of pain reduction, range of motion, and disability. Methodology: The study included 30 subjects who met the selection criteria. Each participant was provided with an explanation of the study and gave informed consent. The participants were randomly divided into two groups. Group A (N=15) received kinesiology taping, replaced every 3 days, along with daily isometric neck exercises for one week. Group B (N=15) underwent interferential therapy combined with daily isometric neck exercises for the same duration. Pre- and post-treatment data on pain, active cervical range of motion, and neck functional disability (measured using the Numerical Pain Rating Scale, Universal Goniometer, and Neck Disability Index) were collected and analyzed using appropriate statistical methods. Results: A comparative analysis using the Whitney U test revealed a statistically significant difference (P<0.05) in the mean scores of the Neck Disability Index, active cervical flexion, and rotation percentage when comparing the post-intervention results between the two groups. The Wilcoxon matched pair test used for pre- and post-test analysis within both groups showed significant changes in the means of NPRS, cervical flexion, extension, rotation, lateral flexion, and NDI. Conclusion: The study concluded that kinesiology taping resulted in significantly greater improvements in the Neck Disability Index, active cervical flexion, and rotation compared to interferential therapy.